DisV-HPV16, versatile and powerful software to detect HPV in RNA sequencing data - Yan, Bingqing (BMC Infect Dis, 2019)
BACKGROUND: The increasing availability of high-throughput sequencing data provides researchers with unprecedented opportunities to investigate viral genetic elements in host genomes that contribute to virus-linked cancers. Almost all of the available computational tools for secondary analysis of sequencing data detect viral infection or genome integration events. However, viral oncogenes expression is likely of importance in carcinoma. We therefore developed a new software, DisV-HPV16, for the evaluation of HPV16 oncogenes expression. RESULTS: HPV16 virus and viral oncogenes expression was detected more rapidly using DisV-HPV16 compared to other software. DisV-HPV16 was proved highly convenient for detecting candidate virus after modification of the reference file. The accuracy of DisV-HPV16 was empirically confirmed in laboratory experiments. DisV-HPV16 exhibited greater reliability than other software. CONCLUSIONS: DisV-HPV16 is a new, dependable software to detect virus and viral oncogenes expression through analysis of RNA sequencing data. Use of DisV-HPV16 can yield deeper, more comprehensive insights into virus infection status and viral and host cell gene expression.